Revisión del género Dichapetalum (Dichapetalaceae) en Costa Rica - Kriebel, Ricardo; Rodríguez, Alexánder (Lankesteriana: International Journal on Orchidology, 2015)
A revision of the Costa Rican species of Dichapetalum (Dichapetalaceae) is presented here. Two new species, D. inopinatum and D. reliquum, are described and illustrated. Discussions, fenological notes and examined specimens are included for the 14 species present in Costa Rica.